Renal biomarkers in chronic kidney disease in felines - Nunes, Sara Veigas (2019)
Chronic kidney disease (CKD) is a progressive disease that is characterized by the occurrence of an irreversible lesion of the nephrons that consequently causes changes in kidney function. It is defined as the most common renal disease in felines. This progressive disease is characterized by the loss of structure and function of one and both kidneys and is a major cause of morbidity and mortality in cats, with prevalence proportional to the age of the animal, affecting approximately 30-50% of geriatric cats. The etiology of this pathological condition is multifactorial and may be attributed to congenital conditions, glomerulopathies or acquired systemic conditions. In clinical practice, CKD is often diagnosed when the animal is already at an advanced stage of disease, which causes therapeutic limitations and may lead to a worse prognosis. CKD staging is performed according to the International Society of Renal Interest (IRIS) recommendations to facilitate appropriate treatment and better monitor the patient. This classification is based on measurement of serum creatinine, proteinuria and systemic blood pressure. In 2015, a new biomarker, Symmetric Dimethylarginine (SDMA) was implemented by the IRIS, for early detection of CKD. The aim of this paper was to conduct a literature review on the current knowledge of renal biomarkers in feline, which may have the potential to be used for early identification of CKD. Current biomarkers have been classified into three subgroups, glomerular function markers, proximal tubular function markers and renal inflammation markers. The identification of new biomarkers for CKD in felines is crucial and aims to be a usefull diagnostic tool with the objective of a better monitoring of cats affected by this condition. Its introduction into clinical practice may contribute to improve current approaches to diagnosis and therapy in veterinary nephrology. However, in order to understand the true value of these markers in CKD approach, further research in veterinary medicine are needed, as the goal of early detection is to increase longevity and improve the prognosis of cats with this condition.